Manual for Project Research - for College and University Students - Lim, Ho Peng (INTI Book Centre Sdn. Bhd., 1992)
Manual for Project Research - for College and University Students is intended as both a classroom text and a reference tool. It is a guide to the methods and materials of research. This Manual is compiled specifically for those who are undertaking research for the first time. The contents of this Manual are presented in a very compact form. The reader is refered to the standard textbook for greater detail and for expended explanations. Attempts were made to offer materials in the Manual that would be applicable to any field. There are, of course, special research tools which have to be utilized in specific fields of specialization. The author felt that it would not be appropriate to include them here. The reference sources listed in the Bibliography at the end of this Manual are recommended for further reading.